Reservoir Bank Erosion Caused and Influenced by Ice Cover. - Gatto,Lawrence W (1982)
The purpose of this study was to evaluate the importance of reservoir bank erosion caused by an ice cover. The evaluation is based on a literature review and on inferences made from field observations and experience. Very little is known about the amount of reservoir band erosion caused by the actions of an ice cover, although considerable information is available on the processess of ice-related erosion along the shorelines or beaches of oceans, rivers or lakes. The importance of ice-related erosion along a reservoir bank seems to be determined primarily by water level. If the reservoir water level is high enough for ice to act directly on the bank face, the amount of erosin caused by ice could be substantial. If the water level is below the bank, ice would have no direct effect on it. However, ice could indirectly increase bank instability by disrupting and eroding nearshore and beach zones, which could lead to bank erosion. (Author)